Interdependent Self-Construal Moderates Relationships Between Positive Emotion and Quality in Social Interactions: A Case of Person to Culture Fit - Kafetsios, Konstantinos G. (Frontiers in Psychology, 2019)
How emotion is experienced and expressed in social encounters can very much depend on a person's cultural orientation and the two can affect the quality of social relationships. The present research examined how an interaction between cultural orientation (person) and emotion in social encounters (situation) can influence social interaction outcomes and by extent, cultural fit. For a period of seven days, participants (N = 164) reported eight positive and eight negative emotions they experienced in naturally occurring social encounters together with indicators of quality of social interaction (satisfaction, attending to the other, perceiving others as emotionally more positive). Results from multilevel random coefficient analyses found that self-construal, interdependence in particular, moderated relationships between positive emotion and social interaction quality. At high levels of positive emotion, higher, compared to lower, interdependence was associated with lower attention to other and lower satisfaction with the encounter. At low levels of positive emotion, higher interdependence was associated with higher social interaction quality than persons lower in interdependence. These effects were more robust when social anxiety was controlled, and social anxiety was highly correlated with participants' interdependent orientation. The results support socially-situated accounts to emotion and cultural constructions of the self, and depict emotion in social interaction as an important indicator of cultural fit.